Sexual Orientation, Social Determinants of Health, and Unmet Substance Use Treatment Need: Findings from a National Survey. (24th November 2020) - Haney, Jolynn L.
Abstract: Background: In 2018, an estimated 89% of individuals who needed treatment for substance use did not have their need met. Compared to heterosexuals, the disparity between needing and receiving treatment is thought to be even higher for sexual minorities. Yet, few studies have investigated sexual orientation and its relationship to unmet treatment need or the association between sexual orientation and specific reasons for the inability to enter treatment. Understanding these reasons is critical to eradicating barriers to treatment for sexual minorities. Obejctives: Using pooled data from the 2015-2018 National Survey of Drug Use and Health and guided by Andersen's behavioral model of health services use, this study examined the relationship between respondents' sexual orientation and their perceptions of reasons for unmet substance use treatment need. Results: Findings indicated that sexual minorities had more than double the odds of having unmet need due to access and insurance barriers. Conclusions: While further research and larger samples are needed to understand the relationships revealed by this study more fully, it is clear that sexual minorities do not have equitable access to substance use treatment services relative to heterosexuals. Implications and directions for future research are discussed.